2023
DOI: 10.3389/fbioe.2023.1130523
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic iron oxide nanoparticle-loaded hydrogels for photothermal therapy of cancer cells

Abstract: Introduction: Non-invasive photothermal therapy (PTT) is a competitive treatment for solid tumors, while the efficacy is largely dependent on the effective retention of photothermal converters in tumor tissues.Methods: Herein, the development of iron oxide (Fe3O4) nanoparticle-loaded alginate (ALG) hydrogel platform for PTT of colorectal cancer cells is reported. Fe3O4 nanoparticles synthesized via coprecipitation method after reaction of 30 min have a small size (61.3 nm) and more suitable surface potential, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Considering the useful magnetic and imaging properties of Fe 3 O 4 nanoparticles and the PTT effect, the developed Fe 3 O 4-ALG-based hydrogel platform may be used as an attractive candidate for MRI and combinational therapy of cancer. [104] Xia and co-workers have developed oxidized dopamine nanoparticles (ODNPs) as promising MRI theranostics with remarkable MRI contrasting capability and photothermal ther- apy (PTT) efficacy. The above theranostic NPs were synthesized via oxidization of dopamine-DTPA-Gd conjugates and poly(ethylene glycol) (PEG)-dopamine conjugates in a one-pot method.…”
Section: Nanotheranosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the useful magnetic and imaging properties of Fe 3 O 4 nanoparticles and the PTT effect, the developed Fe 3 O 4-ALG-based hydrogel platform may be used as an attractive candidate for MRI and combinational therapy of cancer. [104] Xia and co-workers have developed oxidized dopamine nanoparticles (ODNPs) as promising MRI theranostics with remarkable MRI contrasting capability and photothermal ther- apy (PTT) efficacy. The above theranostic NPs were synthesized via oxidization of dopamine-DTPA-Gd conjugates and poly(ethylene glycol) (PEG)-dopamine conjugates in a one-pot method.…”
Section: Nanotheranosticsmentioning
confidence: 99%
“…The above data indicated that the developed Fe 3 O 4 nanoparticle‐loaded hydrogels can be effectively taken up by CT26 cancer cells and can cause significant inhibition in the growth of colorectal cancer cells thereby validating their potential role in therapy of colorectal tumors. Considering the useful magnetic and imaging properties of Fe 3 O 4 nanoparticles and the PTT effect, the developed Fe 3 O 4‐ ALG‐based hydrogel platform may be used as an attractive candidate for MRI and combinational therapy of cancer [104] …”
Section: Mri Contrast Agents As Theranosticsmentioning
confidence: 99%
“…[128] 用共沉淀法合成出小粒径Fe 3 O 4 纳米粒 子, 然后在Fe 3 O 4 纳米粒子上负载ALG (alginate, 海藻 酸盐)水凝胶. 其中, 水凝胶包裹的纳米粒子可以更好 地聚集在肿瘤组织中, 并具有相对较长的停留时间以 发挥更好的治疗效果[129] …”
unclassified